Differential relations among expectancy, task value, engagement, and academic performance: The role of generation status - Edwards, Ordene V.; Dai, Ting (Frontiers in Education, 2023)
Introduction We investigated differences in domain-general expectancy, value, and engagement in school by generation status and how the relationship among these constructs and academic performance differ by generation status. Methods A total of 573 college students enrolled in introductory psychology courses participated in the study. We collected data on generation status, expectancy-value beliefs, school engagement, and official GPA data from participants, tested measurement invariance of expectancy-value beliefs and engagement between first-generation college students (FGCS) and continuing generation college students (CGCS), and conducted multigroup modeling to understand the differential relations of expectancy-value, engagement, and GPA between the two groups. Results We discovered that the latent mean of expectancy beliefs differed significantly by generation status, with FGCS reporting higher expectancy than CGCS. There were no differences in the latent mean of task value. Multigroup structural equation modeling revealed that the effect of expectancy-value motivation on behavioral engagement was similar across groups, but its effect on cognitive engagement was greater for the FGCS than for the CGCS. For both groups, expectancy impacted academic performance via behavioral engagement. Finally, neither expectancy-value motivation nor cognitive engagement directly predicted academic performance for either group. Discussion The findings have important theoretical implications for understanding motivation and achievement of FGCS and CGCS and critical practical implications regarding undergraduate education.